Lawn soil irrigation device - ZHAO MINGSHENG; YANG MENGLAN (2024)
The invention creatively provides a lawn soil irrigation device which comprises a fountain and cameras arranged around the fountain, and further comprises a database, the database comprises sightseeing area information, each camera comprises a camera module, and the camera modules are used for collecting image information in each monitoring view field. The fountain comprises a receiving module, an image analysis module and a control module, the receiving module is used for receiving image information of cameras around the fountain and taking the image information as monitoring image information, and the image analysis module is used for obtaining figure image information, obtaining a figure distance value through analysis according to the image information and sending the figure distance value to the control module. And the control module is used for comparing the figure distance value with sightseeing area information in a database, if the figure distance value falls into the sightseeing area information, a